Assessment of conjunctival microvilli abnormality by micro‐Raman analysis – by G. Rusciano et al. Issue 5 (15th February 2016) - Rusciano, Giulia; Zito, Gianluigi; Pesce, Giuseppe; Del Prete, Salvatore; Cennamo, Gilda; Sasso, Antonio
Abstract : Conjunctival microvilli are microscopic cellular membrane protrusions on apical epithelial cells, which increase the surface area available for tear adherence. Pathological alterations of microvilli structure affect the tear film stability and, conversely, dysfunctions of tear film composition can lead to a suffering epithelium (dry‐eye syndrome). In this work we propose the use of micro‐Raman analysis to reveal conjunctival microvilli abnormalities. Samples were obtained by impression cytology from patients by different stage of dry‐eye syndrome. Our experimental outcomes demonstrate that Raman analysis, combined with the use of Principal Component Analysis, is able to detect different stages of microvilli reduction. Globally, these results hold promise for the use of Raman analysis for an objective, effective, non‐invasive and potentially also in‐vivo analysis of the conjunctiva in all the cases of microvilli‐related ocular pathologies. Abstract : Conjunctival microvilli are microscopic cellular membrane protrusions on apical epithelial cells, which increase the surface area available for tear adherence. Pathological alterations of microvilli structure affect the tear film stability and, conversely, dysfunctions of tear film composition can lead to a suffering epithelium (dry‐eye syndrome). In this work we demonstrated the effectiveness of micro‐Raman analysis to reveal conjunctival microvilli abnormalities in donors affected by dry‐eye syndrome.